Characteristics of Ocular Fundusin Brain Infections at Cipto Mangunkusumo Hospital Jakarta - Maria Jheny Fulgensia Purba; Pradita Sari; Septiana Andri Wardana; Ni Nengah Rida Ariarini; Kartika Maharani; Darma Imran; Riwanti Estiasari (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2023)
Background: Brain infections (BI) may cause optic nerve abnormalities. Awareness on optic nerve abnormalities will be useful in assisting further management. The characteristics of the ocular fundus (fundus) in BI have not been widely studied in Indonesia. Objective: This study aimed to apprehend the depiction of the fundus in BI in Cipto Mangunkusumo Hospital Jakarta (RSCM). Methods: Cross-sectional study was conducted on October-December 2021 at RSCM. Inclusion criteria: BI patients who had fundas results. Exclusion criteria: fundas results cannot be interpreted. Images from 20D-lens fundoscopy were captured with a digital camera. Captured images were then interpreted by three examiners in disguise. Results are analyzed if there are similarities between at least two examiners. Results: Among 49 subjects, 25 had normal fundus. Abnormalities were found in 8 subjects: 4 (12.1%) papilledema, 3 (9.1%) papillatrophy, and 1 (3%) retinal hemorrhage. The highest mean aperture pressure was in the papillatrophy group (37 cmH2O), followed by papilledema (27 cmH2O). Cryptococcal meningitis caused papilledema in 60% of cases. Of BI cases with mortality, 80% were tuberculous meningitis with normal fundus. BI can increase ICP, but only 12.1% had papilledema. Papillatrophy indicated prolonged ICP elevation. The highest mortality was in the normal fundus group, suggesting papilledema alone is not a definitive predictor of poor prognosis due to confounding factors. Conclusion: Although BI causes an increase in ICP, papilledema is not always found. High aperture pressure was found in the papillatrophy group, but the highest mortality was found in the normal fundus group.